Diagnostics, monitoring and outpatient care in children with suspected pulmonary hypertension/paediatric pulmonary hypertensive vascular disease. Expert consensus statement on the diagnosis and treatment of paediatric pulmonary hypertension. The European Paediatric Pulmonary Vascular Disease Network, endorsed by ISHLT and DGPK. (6th April 2016) - Lammers, Astrid E; Apitz, Christian; Zartner, Peter; Hager, Alfred; Dubowy, Karl-Otto; Hansmann, Georg
Abstract : Pulmonary hypertension (PH) is a condition of multiple aetiologies with underestimated prevalence and incidence. Indeed, despite access to modern therapies, pulmonary hypertensive vascular disease (PHVD) remains a progressive, usually life-limiting condition, severely impacting on the patients' well-being. We herein provide practical, expert consensus recommendations on the initial diagnostic work-up, clinical management and follow-up of children and adolescents with PH/PHVD, including a diagnostic algorithm. The major topics and methods that need to be tailored and put into context of the individual patient include PH classification, clinical signs and symptoms, basic diagnostic and advanced imaging measures (ECG, chest X-ray, transthoracic echocardiography, cardiac magnetic resonance, chest CT angiography, cardiac catheterisation, ventilation-perfusion lung scan, abdominal ultrasound), lung function tests, 6 min walk and cardiopulmonary exercise testing, sleep study (polysomnography), laboratory/immunological tests, considerations for elective surgery/ general anaesthesia, physical education and exercise, flying on commercial airplanes, vaccinations, care of central intravenous lines and palliative care. Due to the complexity of PH/PHVD, the clinical care has to be multidisciplinary and coordinated by a dedicated specialist paediatric PH centre, not only to decrease mortality but to allow children with PH/PHVD to reach a reasonable quality of life.